Media use degree and depression: A latent profile analysis from Chinese residents - Gong, Fangmin; Yi, Pei; Yu, Lian; Fan, Siyuan; Gao, Guangze; Jin, Yile; Zeng, Leixiao; Li, Yang; Ma, Zheng Feei (Frontiers in Psychology, 2023)
Background: Previous studies have emphasized the media as an essential channel for understanding information about depression. However, they have not divided groups according to the degree of media use to study their differences in depression. Therefore, this study aims to explore the influence of media use on depression and the influencing factors of depression in people with different media use degrees. Methods: Based on seven items related to media use, a total of 11, 031 respondents were categorized by the frequency of media use using latent profile analysis (LPA). Secondly, multiple linear regression analyses were conducted to analyze the effects of depression in people with different degrees of media use. Finally, factors influencing depression among people with different degrees of media use were explored separately. Results: All respondents were classified into three groups: media use low-frequency (9.7%), media use general (67.1%), and media use high-frequency (23.2%). Compared with media use general group, media use low-frequency (β = 0.019, P = 0.044) and media use high-frequency (β = 0.238, P < 0.001) groups are significantly associated with depression. The factors influencing depression in the population differed between media use low-frequency, media use general, and media use high-frequency groups. Conclusion: The government and the appropriate departments should develop targeted strategies for improving the overall health status of people with different media use degrees.